2010
DOI: 10.1177/0883073810371228
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Epileptiform Discharges in the Sleep-Deprived Electroencephalogram in Children Evaluated for Attention-Deficit Disorders

Abstract: The authors determined the frequency of epileptiform discharges in the electroencephalogram (EEG) of a cohort of children and adolescents referred to a neurology specialty clinic for evaluation of attention-deficit disorders. Of 624 records, 461 (73.9%) were normal and 163 (26.1%) abnormal. Of abnormal EEGs, 70 (42.9%) had focal epileptiform discharges only, 68 (41.7%) had generalized epileptiform discharges only, and 19 (11.6%) had both independent focal and generalized spikes. Focal spikes were localized chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 20 publications
2
24
0
2
Order By: Relevance
“…The wide variation in the frequency of EEG abnormalities may be due to different research methods, duration of EEG, EEG activation, and the enrolled study subjects. In this retrospective study, the prevalence of EEG abnormalities among non-epileptic children with ADHD was 23.1%, which is similar to the average rate of eight studies (26.1%) summarized by Millichap et al [16] Compared to studies with awake only [15] or a lack of EEG studies, [13] the prevalence of EEG abnormalities in the current study is higher. However, the prevalence of abnormal EEG recordings in the current study is lower than that in studies with prolonged sleep recordings [20] or sleep-deprived EEGs [14,16].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The wide variation in the frequency of EEG abnormalities may be due to different research methods, duration of EEG, EEG activation, and the enrolled study subjects. In this retrospective study, the prevalence of EEG abnormalities among non-epileptic children with ADHD was 23.1%, which is similar to the average rate of eight studies (26.1%) summarized by Millichap et al [16] Compared to studies with awake only [15] or a lack of EEG studies, [13] the prevalence of EEG abnormalities in the current study is higher. However, the prevalence of abnormal EEG recordings in the current study is lower than that in studies with prolonged sleep recordings [20] or sleep-deprived EEGs [14,16].…”
Section: Discussionsupporting
confidence: 87%
“…Electroencephalography (EEG) has been used to evaluate electrical activity in the brain for some time, and several studies have demonstrated a high incidence of epileptic seizures and EEG abnormalities in children with ADHD [13][14][15][16][17]. Hemmer et al [13] reported the presence of epileptiform discharges in 36(15.4%) of 234 children with ADHD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A more objective test such as EEG if validated could be a valuable aid in the diagnosis and management of ADHD. The significance of seizure discharges in approximately 25% of sleep-deprived EEGs in ADHD children is further evidence of the utility of the EEG in ADHD management [3]. …”
mentioning
confidence: 98%